Genetic Variability, Character Association and Path Coefficient Study in Guava (Psidium guajava L.) for Plant Growth, Floral and Yield Attributes - Patel, R. K.; Maiti, C. S.; Deka, Bidyut C.; Vermav, V. K.; Deshmukh, N. A.; Verma, M. R. (International Journal of Bio-resource and Stress Management, 2015)
Guava (Psidium guajava L.) is one of the major fruit crops of India. The present investigation was carried out with eleven genotype of guava under mid-hill subtropics of Meghalaya during 2011 and 2012 with respect to plant growth, floral and yield related traits. Being an open pollinated and heterozygous crop, wide range of phenotypic variation along with high heritability and genetic advance has been observed among the genotypes. High heritability estimates associated with high genetic advance as % of mean were obtained for fruit yield which indicated that selection of this character would be more effective. Such association may be attributed to the action of additive genes. This character also exhibited high gcv, therefore, selection based on phenotypic performance for this trait would be effective in improving directly in the population. Association studies revealed that fruit yield was significantly and positively correlated with plant height, stem diameter, canopy spread, shoot diameter, number of leaves, days to flowering, fruit set, bud length, bud diameter, petal length, stamen length, number of stamens flower-1 and pistil length at both genotypic and phenotypic levels while, with flowering duration, fruit drop, number of petals flower-1 and petal width at genotypic level. Positive direct effect of petal length, bud length, plant height, bud diameter, stamen length, number of leaves shoot-1, petal width, pistil length, days to flowering, flowering duration, fruit drop, fruit set, stem diameter, canopy spread along with significant and positive correlation with fruit yield suggested that these traits must be given due importance while selecting a genotype.